Rationale for Targeted Confectionery Products for Children over Three Years Old - Misteneva Svetlana Yu.; Savenkova Tatiana V.; Demchenko Elena A.; Shcherbakova Natalia A.; Gerasimov Timofey V. (Техника и технология пищевых производств)
Introduction. According to the World Health Organization, unhealthy diets are a major risk for noncommunicable diseases. These risks begin in childhood and develop throughout life. Scientists around the world are busy establishing optimal requirements for children’s diet that would contribute to their healthy development throughout the entire period of growing up. The quality of nutrition in childhood is a critical factor, since the physiological need for nutrients and energy during this period is especially high. Nutrition for preschool and school age children has its own specifics, e.g. lack of variety and functional products, preference for products with a high content of added sugar, fat, and salt, etc. Results and discussion. The article summarizes various recommendations on nutrition and physiological requirements for basic nutrients and energy. The recommendations are based on modern research on the nature and structure of children’s diet in Russia and abroad. The authors analyzed the Unified Register of State Registration Certificates of targeted functional foods. The paper also describes the main directions of improving the formulation of targeted confectionery products for preschool and school age children, based on taking global trends and principles of healthy eating. Conclusion. Most confectionery products have extreme content of critical substances, high energy value, and almost no dietary fiber, vitamins, or mineral matter. Therefore, new formulations of targeted confectionery products for children over three years of age are relevant and promising if developers take into account the principles of healthy nutrition. The existing regulatory framework for the production and sale of this group of products requires improvement.